Developing literacy or focusing on interaction: New Zealand students' strategic efforts related to Chinese language learning during study abroad in China. (June 2021) - Yang, Gong Frank; Quanjiang, Guo; Michael, Li; Chun, Lai; Chuang, Wang
Abstract: This paper reports on an inquiry that interpreted a group of New Zealand students' strategic efforts related to Chinese language learning during study abroad in China through the lens of identity. In this study, we encouraged 15 participants to write reflective journals and conducted group interviews and online communication to examine their strategic efforts to learn Chinese. The analysis revealed that the participants' identity imaginations were closely associated with their strategic learning efforts across different settings, including literacy-oriented strategic efforts in the classroom and interaction-oriented strategic efforts outside the classroom. The findings also suggest that the participants made strategic efforts to seek opportunities and resources for practicing spoken Chinese outside the classroom because they were positioned in undesirable ways by instructors and course content in the classroom. These findings offer insights into the crucial role of learner identity in mediating language learners' strategic efforts during study abroad in China. They imply that formal learning in the classroom needs to be synergized by informal learning outside the classroom, and educational stakeholders should revise the traditional design of study abroad programs to better support international students' language learning efforts.